Constucted Wetland sebagai Model Ruang Publik untuk Memperbaiki Ekologi pada Kawasan Permukiman di Tepian Sungai Kapuas Pontianak - Jockie Zudhy Fibrianto; Muhammad Subhansyah Ikram; Caesar Destria (Politeknik Negeri Pontianak, 2022)
The residential areas on the banks of the Kapuas River have a poor domestic sewage system. Domestic waste that pollutes the Kapuas River needs to be filtered before entering the river. Constructed wetland is a solution for filtering hydrological waste by using water plants. Hydrological analysis related to tides and levels of river water quality as well as analysis of endemic water vegetation are the basis for determining the concept of a constructed wetland model which ecologically functions to filter waste, and also socially functions as a public space. With a suitable constructed wetland design, it is hoped that it can improve the ecology of the residential area on the banks of the Kapuas River and can also become a public space destination for people in residential areas on the banks of the Kapuas. This research produces a visual prototype of constructed wetlands in the area, and this research is also expected to produce outputs in the form of research reports, national journal publications and Appropriate Technology, which can be adopted by the government or society.